Less than five is less than ideal: replacing the “less than 5 cell size” rule with a risk-based data disclosure protocol in a public health setting - Wilkinson, Krista (Can J Public Health, 2020)
SETTING: The Winnipeg Regional Health Authority (WRHA) is one of the largest and most diverse health regions in Canada. Within the WRHA, the Population and Public Health (PPH) Surveillance Team provides epidemiological support across a variety of public health service areas. INTERVENTION: We developed and deployed a risk-based data disclosure protocol that balances the need to share public health surveillance data with the need to protect personal health information. OUTCOMES: Unlike the conventional data disclosure standard adopted in Manitoba (suppress cell sizes < 5), the new protocol is based upon a risk-based re-identification approach that focuses on the size of the denominator instead of the numerator. This approach has allowed for innovation in data dissemination infrastructure within the unit that would not have been possible previously, including the deployment of public-facing cloud-based interactive maps and dashboards. It has also resulted in strengthened protection of personal health information as the risk of re-identification can now be precisely calculated across all data release situations. IMPLICATIONS: In challenging the “cell size less than five” rule, this project is an example of how a scientifically based data disclosure protocol can support a public health organization in meaningful sharing of population health data with community partners and the public. This helps ensure that program and policy responses are empirically based, strategically focused, and cross-jurisdictionally coordinated. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.17269/s41997-020-00303-8) contains supplementary material, which is available to authorized users.